2012
DOI: 10.2319/060411-367.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of root resorption following rapid maxillary expansion using cone-beam computed tomography

Abstract: Objective: To evaluate the root resorption after rapid maxillary expansion (RME) via cone-beam computed tomography (CBCT). Materials and Methods: Records of 25 patients who had undergone RME with tooth-borne banded expander were obtained from the archive of the orthodontic department. CBCT data were reconstructed with surface and volume rendering, and the volumetric images were manipulated to display the root surfaces from various orientations. On these three-dimensional images, permanent first molars and firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 23 publications
3
91
0
7
Order By: Relevance
“…We found statistically significant resorption in P1. In this study the amount of resorption in our first premolars was more than Baysal et al 5 had evaluated root resorption volumetrically with CBCT after RME. In our opinion, the difference was due to including the cervical region in our volumetric assessment.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…We found statistically significant resorption in P1. In this study the amount of resorption in our first premolars was more than Baysal et al 5 had evaluated root resorption volumetrically with CBCT after RME. In our opinion, the difference was due to including the cervical region in our volumetric assessment.…”
Section: Resultsmentioning
confidence: 91%
“…[16][17][18] As of today, there has been only one study evaluating root resorption after RME with CBCT in vivo. 5 The volumetric data set comprises isotropic structures, known as voxels, each representing a specific degree of X-ray absorption. 19 When the CBCT images were compared with micro CT and laser scanning, the authors found that volumetric measurements made with CBCT were all similar for voxel sizes up to 200 mm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All these studies confirm the reliability and accuracy of the high resolution 3D images of the cone beam and show how valuable it is as a tool for detecting resorption 3,21,24,28 .…”
Section: How To Detect Oiirr: Input From the Cone Beammentioning
confidence: 48%